Open-Ended Toys to Stimulate Cognitive Development Children Aged 1-3 Years Old in the Pandemic Era - Nurul Fitriana Bahri; Alvian Fajar Setiawan (Universitas Pendidikan Indonesia (UPI), 2022)
Cognitive development is one of the important aspects related to the stages of a child's ability to acquire interpretation and knowledge based on experience and information obtained. One of ways to stimulate children's cognitive development is through the use of open-ended toys. Open-ended toys are a type of toys that provides space for interpretation and can be used in various ways, thereby triggering children's creativity. The purpose of this research was to analyze the use of open-ended toys in stimulating the cognitive development of children aged 1-3 years old in the pandemic era. The method used in this study is qualitative, namely a descriptive analysis of the function aspect of three kinds open-ended toys. Data obtained through literature study, observation, interviews, and documentation. In this research, theory about the stages of children's play development according to Piaget was used. Based on the results of the analysis, it can be seen open-ended toys in the form of puzzles, building blocks, and animal figurines can stimulate children's cognitive development by increasing children's concentration range, language skills, fine motor skills, and gross motor skills in children aged 1-3 years old in the era of the covid-19 pandemic.